Characterization and Modification of Ni-rich Cathode Materials for Li-ion Battery - Qu, Jingyi (My University, 2024)
With the rapid advancement of electric vehicles (EVs), there is an urgent need for extensive research on lithium-ion batteries (LIBs), which are integral to EV performance. Among the critical components of LIBs, the cathode plays an essential role in determining the battery's capacity, rate capability, cycle life, and cost. However, research in this area has recently encountered a bottleneck. The application of cathodes in LIBs is constrained by the limitations of cathode materials, which fundamentally influence electrochemical performance. Consequently, this project aims to conduct a comprehensive investigation into cathode materials and their degradation mechanisms during electrochemical cycling, utilizing advanced characterization techniques. In this thesis, Chapter 1 provides a brief introduction to the background, motivations, outline, and publication contributions related to this project. Chapter 2 offers an overview of lithium-ion batteries, discussing essential components and their respective materials. It also dives into the degradation mechanisms of Ni-rich ternary transition-metal oxides, which are considered a very promising cathode material in the industry. Chapter 3 introduces advanced characterization techniques, accompanied by relevant examples, including scanning and transmission electron microscopy, energy-dispersive X-ray spectroscopy, electron energy loss spectroscopy, X-ray absorption spectroscopy, X-ray diffraction, and electrochemical impedance spectroscopy. The following three chapters present in-depth investigations into the structural degradation mechanisms of the LiNi0.8Mn0.1Co0.1O2 (NMC811) cathode during and after cycling. Chapter 4 focuses on the phase transition during cycling in NMC811, a process of significant importance due to its impact on structural evolution and degradation mechanisms. This chapter describes an in-operando study of NMC811 as a cathode cycled in a customized coin cell for in-operando XRD. We captured heterogeneous phase transition behaviors at various locations within the NMC811 cathode. To address the complexity of the results, we employed a machine learning-assisted approach to disentangle the highly overlapping phase components and track each one throughout cycling. This approach has substantially enhanced our understanding of heterogeneous phase evolution from both surface and bulk perspectives. Additionally, in-operando XRD has proven to be an excellent technique for monitoring phase evolution within the bulk of the material. Concerned about heterogeneity, NMC811 is also known as air sensitive. Exposure to ambient environments can detrimentally affect its surface structure. To mitigate this degradation, we synthesized lithium boron carbon oxide (LBCO) and applied it as a coating on the NMC811 secondary particles using a sol-gel method. Through optimization of the coating concentration and processing parameters, the degraded surface of NMC811 was regenerated and stabilized, resulting in a thinner damaged layer. Furthermore, after prolonged cycling up to a severe condition voltage, structural characterization of the NMC811 revealed that the LBCO coating significantly prevented severe deterioration of the interior structure compared to air-exposed NMC811. For a wider application of NMC811 as cathodes in LIBs, in response to the growing demand for fast charging, Chapter 6 presents an in-depth study of the degradation mechanisms of NMC811 under different charging rates. This chapter elucidates that the degradation of NMC811 during fast charging is a complex process, primarily driven by Li ion loss in the bulk of primary particles, cracking, and the formation of the cathode-electrolyte interphase. In our investigation of cracking, we examined both microcracks and nanocracks, with their origins and development characterized by multiscale and versatile techniques. Lastly, Chapter 7 summarizes the key findings of this thesis, highlighting the most significant contributions for the field. It also explores potential future research directions, offering predictions and suggestions for further investigation.
Keywords: Li-ion battery; Electron microscopy; Ni-rich cathode materials; Spectroscopy